Relationships between sources of acid mine drainage and the hydrochemistry of acid effluents during rainy season in the Iberian Pyrite Belt - Perez-Ostalé, E. (2016)
In the Iberian Pyrite Belt (IPB), southwest Spain, a prolonged and intense mining activity of more than 4,500 years has resulted in almost a hundred mines scattered through the region. After years of inactivity, these mines are still causing high levels of hydrochemical degradation in the fluvial network. This situation represents a unique scenario in the world, taking into consideration its magnitude and intensity of the contamination processes. In order to obtain a benchmark regarding the degree of acid mine drainage (AMD) pollution in the aquatic environment, the relationship between the areas occupied by the sulfide mines and the characteristics of the respective effluents after rainfall was analysed. The methodology developed, which includes the design of a sampling network, analytical treatment and cluster analysis, is a useful tool for diagnosing the contamination level by AMD in an entire metallogenic province, at the scale of each mining group. The results presented the relationship between sulfate, total dissolved solids and electrical conductivity, as well as other parameters that are typically associated with AMD and the major elements that compose the polymetallic sulfides of IPB. This analysis also indicates the low level of proximity between the affectation area and the other variables.